N-vinylpyrrolidone/acrylic acid/2-acrylamido-2-methylpropane sulfonic acid based hydrogels: Synthesis, characterization and their application in the removal of heavy metals - KÖK YETİMOĞLU, ECE; KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (ELSEVIER, 2007)
In this work, the synthesis of N-vinylpyrrolidone/acrylic acid/2-acryl amido-2-methylpropane sulfonic acid (NVP/AAc/ AMPS) based hydrogels by UV-curing technique was studied and their swelling behavior, heavy metal ion recovery capabilities were investigated. The structures of hydrogels were characterized by FT-IR analysis and the results were consistent with the expected structures. Thermal gravimetric analysis of hydrogels showed that the thermal stability of hydrogel decreases slightly with incorporation of AMPS units into the structure. In addition, the morphology of the dry hydrogel sample was examined by SEM. According to swelling experiments, hydrogels with higher AMPS content gave relatively higher swelling ratio compared to neat hydrogel. These hydrogels were used for the separation of Cd(II), Cu(II) and Fe(III) ions from their aqueous solutions. The influence of the uptake conditions such as pH, time and initial feed concentration on the metal ion binding capacity of hydrogel was also tested. The selectivity of the hydrogel towards the different metal ions tested was Cd(II) > Cu(II) > Fe(III). It was observed that the specific interaction between metal ions and ionic comonomers in the hydrogel affected the metal binding capacity of the hydrogel. The recovery of metal ions was also investigated in acid media. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: hydrogel; 2-acrylamido-2-methylpropane sulfonic acid; UV-curing; adsorption; heavy metal; SUPERABSORBENT HYDROGELS; COPOLYMER HYDROGEL; SWELLING BEHAVIOR; POLYACRYLAMIDE; RADIATION; IONS; POLYMERIZATION; ADSORPTION